The Effect of Augmented Reality Virtual Try-On on Purchase Intention Mediated by Perceived Enjoyment (Study on Revlon Products in Denpasar City) - Mohamad Ardiansyah Wahyudin; Aksari, Ni Made Asti (Asian Journal of Management Analytics, 2024)
This study aims to examine and explain the effect of augmented reality virtual try-on on purchase intention mediated by perceived enjoyment of Revlon products on Shopee. Using purposive sampling, this research was conducted on 130 women in Denpasar City who are cosmetic users and Shopee application users. Data collection was carried out through the distribution of questionnaires both offline and online via Google Forms. This study used path analysis techniques and the Sobel test. The findings indicate that augmented reality virtual try-on have a positive and significant effect on purchase intention and perceived enjoyment. Perceived enjoyment also has a positive and significant effect on purchase intention. Furthermore, perceived enjoyment can mediate the effect of augmented reality virtual try-on on purchase intention. If the virtual try-on feature effectively stimulates user engagement, it enhances the perceived enjoyment of the experience, which subsequently leads to a positive response in the form of increased purchase intention. It is recommended that Revlon ensure the color accuracy of the virtual try-on feature closely matches the actual product colors. Additionally, Revlon should consider providing feedback to Shopee to improve the feature's realism, detail, and interactivity.